Assessing the spatial distribution patterns of suitable inland valleys for rice development: a case study of two contrasting regions in Benin - Djagba, J. F.; Dossou‑Yovo, E. R.; Sintondji, L. O.; Vissin, E. W.; Zwart, Sander J. (Springer, 2024)
To increase rice production in Africa, both intensification and area expansion are needed. Inland valley (IV) agroecosystems are important for rice production due to their relatively high water availability and soil fertility. However, the spatial distribution of suitable IVs remains uncertain. The objective of this study was to model spatial distribution patterns of suitable IV areas for rice production. Biophysical, socioeconomic and management practice data were collected from 242 IVs in two contrasting regions in Benin, namely, the Departments of Mono and Couffo (Mono-Couffo) and the Upper Ouémé River catchment (Upper Ouémé). Geographically weighted regression (GWR) and ordinary least squares (OLS) models were used to predict the spatial distribution of suitable IV areas for rice production. The results showed that the GWR model performed better than the OLS model in assessing the IV suitability spatial distribution. There were 177,714 ha (46%) and 431,954 ha (31%) of highly suitable IVs for rice production in Mono-Couffo and Upper Ouémé, respectively. The most significant variables for predicting suitable IV areas for rice production were irrigation water resources, soil fertility management and total nitrogen in topsoil in Mono-Couffo and the number of male farmers in the IV, shallow water table duration at the IV bottom, and elevation in Upper Ouémé. These results demonstrated the effectiveness of the GWR model in assessing the distribution of highly suitable IVs.